The influence of a hotel room experience and loyalty recognition of guests by employees on overall guest satisfaction in IHG hotels - Lončar, Jovana; Knežević, Miroslav (The Business of Tourism, 2023)
The subject of this research is guest satisfaction in IHG hotels (Intercontinental Hotels Group). Various factors affect the overall evaluation of guest satisfaction and experience. The aim of the research is to determine whether the experience of the hotel room as a basic hotel product is more important for guest satisfaction, or the feeling that they are recognized by employees as loyal guests and that they receive the treatment they expect. In the literature review, papers that analysed guest satisfaction were referred to. Data used for the research was taken from customer experience platform Medallia1, and then the average score for different categories was analysed from questionnaires that were sent to members of the loyalty program IHG One Rewards after their check out from the hotel during the year 2022. 89 IHG hotels were included in the survey. Guests evaluated overall satisfaction with their stay in the hotel, as well as individual aspects. According to the results of the study both overall guest room experience and loyalty recognition have positive impact on overall experience. However, the stronger impact on guest satisfaction has experience of a hotel room- the main hotel product.
Keywords: guest satisfaction; guest experience; loyality; hotel; hotel room